Assessment of turcicum leaf blight development in maize genotypes - and YASHODA HEGDE, S.I. HARLAPUR*, M.S. KULKARNI, SRIKANT KULKARNI, M.C. WALI (Indian Phytopathology, 2008)
Field experiments were conducted to study the turcicum blight response of 30 maize genotypes. Based on latent period, lesion density, lesion size, apparent rate of infection and area under disease progress curve (AUDPC), the various components of blighting, genotypes Allrounder, IB-8501, Cargill 900M, Hi-Shell, NAC-6004, C-111, KH-517, Kaveri 235 and NK-6240 were identified as slow blighters. Genotypes CM-202, GS2, PEMH-2 and Amber Pop Corn were considered as fast blighters and susceptible. Correlation studies indicated that latent period showed highly significant and negative correlation with per cent disease index (PDI), whereas lesion density and lesion size components showed significant and positive correlation with per cent disease index and AUDPC. The multiple regression (R2 ) values for PDI and AUDPC were 0.86 and 0.87, respectively.